Omprojektering av parkeringsytor : en väg mot multifunktionella gröna ytor - Carlsson, Linn; Björfors, Daniel; Persson, Jessica (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
Densification that takes place in both Sweden and the rest of the world can lead to the nature around the cities being protected but can also mean that greenery and good habitats within the cities are lost. In the discussion about densification, the handling of unused surfaces is a factor. Many of these unused surfaces are parking spaces in residential areas that are in poor condition and in need of refurbishment. This study has dealt with whether the right design and choice of materials when reprocessing unused parking surfaces can lead to multifunctional surfaces. Surfaces that, through increased ecosystem services, are in line with sustainable urban construction.